Shotgun proteomics suggests involvement of additional enzymes in dioxin degradation by Sphingomonas wittichii RW1. (30th September 2013) - Hartmann, Erica M.; Armengaud, Jean
Summary Chlorinated congeners of dibenzo‐p‐dioxin and dibenzofuran are widely dispersed pollutants that can be treated using microorganisms, such as the Sphingomonas wittichii RW1 bacterium, able to transform some of them into non‐toxic substances. The enzymes of the upper pathway for dibenzo‐p‐dioxin degradation in S. wittichii RW1 have been biochemically and genetically characterized, but its genome sequence indicated the existence of a tremendous potential for aromatic compound transformation, with 56 ring‐hydroxylating dioxygenase subunits, 34 extradiol dioxygenases and 40 hydrolases. To further characterize this enzymatic arsenal, new methodological approaches should be employed. Here, a large shotgun proteomic survey was performed on cells grown on dibenzofuran, dibenzo‐p‐dioxin and 2‐chlorodibenzo‐p‐dioxin, and compared with growth on acetate. Changes in the proteome were monitored over time. In total, 502 proteins were observed and quantified using a label‐free mass spectrometry‐based approach; all data were deposited to the ProteomeXchange (PXD000403). Our results confirmed the roles of the dioxin dioxygenase DxnA1A2, trihydroxybiphenyl dioxygenase DbfB, meta‐cleavage product hydrolase DxnB and reductase RedA2, and corroborated the proposed involvement of the Swit_3046 dioxygenase and DxnB2 hydrolase. Trends across substrates and over the course of growth do not support concerted pathway regulation and suggest the involvement of an additional hydrolase and several TonB‐dependent receptors.